2006
DOI: 10.1097/01.jcp.0000203195.65710.f0
|View full text |Cite
|
Sign up to set email alerts
|

Reboxetine Versus Fluvoxamine in the Treatment of Motor Vehicle Accident-related Posttraumatic Stress Disorder

Abstract: Study observations indicate comparable efficacy of reboxetine and fluvoxamine in the management of MVA-related PTSD despite reboxetine's selective noradrenergic activity. Reboxetine appears to be at least as effective as fluvoxamine and may offer an alternative management option in this often difficult-to-treat and disabling condition. A lower and flexible reboxetine dosing schedule will be recommended for future research to improve its tolerability in PTSD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The superior tolerability profile for SRIs over tricyclic antidepressants, the emergence of definitive pharmacotherapy trials supporting the efficacy of SRIs for PTSD (Brady et al, 2000;Marshall et al, 2001;Tucker et al, 2001), the absence of definitive NRI trials for PTSD, and the negative preliminary findings with desipramine (Reist et al, 1989), all contributed to waning interest in NRI treatment for PTSD. More recently, the emergence of drugs that block the a 1 noradrenergic receptor, such as prazosin (Raskind et al, 2007) and risperidone (Berger et al, 2009;Rothbaum et al, 2008) as promising treatments for the re-experiencing and hyperarousal symptoms of PTSD, converges with evidence of (a) the capacity of NRIs to attenuate noradrenergic activation (Charney and Heninger, 1985) and (b) of preliminary support for the NRI, reboxetine for PTSD (Spivak et al, 2006). These findings indicate that after 25 years of research, noradrenergic hyperactivity remains an important target for the treatment of PTSD ( Van der Kolk, 2004).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The superior tolerability profile for SRIs over tricyclic antidepressants, the emergence of definitive pharmacotherapy trials supporting the efficacy of SRIs for PTSD (Brady et al, 2000;Marshall et al, 2001;Tucker et al, 2001), the absence of definitive NRI trials for PTSD, and the negative preliminary findings with desipramine (Reist et al, 1989), all contributed to waning interest in NRI treatment for PTSD. More recently, the emergence of drugs that block the a 1 noradrenergic receptor, such as prazosin (Raskind et al, 2007) and risperidone (Berger et al, 2009;Rothbaum et al, 2008) as promising treatments for the re-experiencing and hyperarousal symptoms of PTSD, converges with evidence of (a) the capacity of NRIs to attenuate noradrenergic activation (Charney and Heninger, 1985) and (b) of preliminary support for the NRI, reboxetine for PTSD (Spivak et al, 2006). These findings indicate that after 25 years of research, noradrenergic hyperactivity remains an important target for the treatment of PTSD ( Van der Kolk, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…A small, negative trial with desipramine in combat-related PTSD (Reist et al, 1989) was followed by a randomized comparison that showed the NRI reboxetine was of equal efficacy to an SRI (Spivak et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fluvoxamine demonstrated efficacy for PTSD in open trials [979-983], and in a RCT was as effective as reboxetine (Level 2) [984]. …”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Responders to the DBPC study sustained their initial response, and patients who failed in the initial study could become responders (Londborg et al 2001)(A). Á The SSRI fluvoxamine was as effective as reboxetine, a norepinephrine reuptake inhibitor (Spivak et al 2006…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%